A proteção dos direitos humanos dos refugiados em Goiás: uma análise sobre a formulação de políticas públicas - Aguiar, Rafaella Ribeiro de (2019)
This research analyzes the influence of the formulation of a public policy for migrants, refugees and stateless persons in the State of Goiás on the local integration of refugees from a qualitative study, emphasizing the formulation process carried out from 2016 to 2018 and the actors involved in it. Believes that public policy design should involve implementers in the formulation process (Howlett, 2013; Ansell & Sorensen, 2017). It analyzes the context based on two fronts of technical and methodological exploration: i) a documentary analysis, involving the revision of the norms of international Human Rights, International Refugee Law and the national laws about migration; and the meeting records of the Thematic Committee of the Intersectoral Committee of Public Policies for Migration in the State of Goiás (in portuguese, CIPEMIGRA); and ii) the interviews with the members of CIPEMIGRA, the ones responsible for the formulation. Finally, it seeks to understand and analyze the policy-making process and its content in the light of human rights in an attempt to understand its relationship to refugee protection and local integration.